Ovatrine, a compound from plant extracts, used for female infertility treatment and increase the number of ovarian follicles - Hussein, Mahmoud Elnahas (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Recently natural products extracted from medical plants are very important in the field of alternative medicine. Glycosides, flavonoids and polyphenols are components of natural molecules have several health benefits such as anti-inflammatory, anti-oxidants, and have many ameliorative roles against male and female reproductive system intractable disorders. Objective of this study was to the compound of the plant extracts blend which is rich with glycosides, flavonoids and polyphenols was named as Ovatrine. The safety as well as the efficacy of some medical plants extracts on the fertility of the female mice was investigated using Ovatrine. Methods: Firstly, the safety of Ovatrine was evaluated using some mice and the levels of the follicle stimulating hormone in the serum of the treated animals with Ovatrine was evaluated using biochemical tests. Also, the effects of the Ovatrine on the histological parameters of the treated ovary and uterus were evaluated using histological analysis. Results: The animals treated with Ovatrine were healthy and did not show any signs of mortality, toxicities and there were no blood contents changes. Additionally, follicle stimulating hormone level in the serum increased after administration with Ovatrine twice a day for 30 days as compared with the non-treated animals. Furthermore, the histological structures of the ovary and uterus improved in the mice treated with Ovatrine compared with that in the non-treated mice. Conclusions: In general glycosides, flavonoids and polyphenols, which were found in the Ovatrine in a higher concentration, have important health benefits such as antioxidant, anti-inflammatory and improve the fertility in the female mice. In the future this study will be very important for drug development which composed mainly from safe natural products and used for infertility and intractable diseases treatment.